Distinct Time-Course of Alterations of Groups I and II Metabotropic Glutamate Receptor and GABAergic Receptor Expression Along the Dorsoventral Hippocampal Axis in an Animal Model of Psychosis - Dubovyk, Valentyna; Manahan-Vaughan, Denise (Frontiers in Behavioral Neuroscience, 2019)
Psychosis is a clinical state that encompasses a range of abnormal conditions, including distortions in sensory information processing and the resultant delusional thinking, emotional discordance and cognitive impairments. Upon developing this condition, the rate at which cognitive and behavioral deteriorations progress steadily increases suggesting an active contribution of the first psychotic event to the progression of structural and functional abnormalities and disease establishment in diagnosed patients. Changes in GABAergic and glutamatergic function, or expression, in the hippocampus have been proposed as a key factor in the pathophysiology of psychosis. However, little is known as to the time-point of onset of putative changes, to what extent they are progressive, and their relation to disease stabilization. Here, we characterized the expression and distribution patterns of group I and II metabotropic glutamate (mGlu) receptors and GABA receptors one week and three months after systemic treatment with an NMDAR antagonist (MK801) that initiates a psychosis-like state in adult rats. We found an early alteration in the expression of mGlu1, mGlu2/3 and GABA B receptors across the hippocampal dorsoventral and transverse axes. This expanded to include an up-regulation of mGlu5 levels across the entire CA1 region and a reduction in GABA B expression, as well as GAD67-positive interneurons particularly in the dorsal hippocampus that appeared 3 months after treatment. Our findings indicate that a reduction of network excitation may occur in the hippocampus soon after first-episode psychosis. This changes, over time, into increased network excitability. These hippocampus-specific alterations are likely to contribute to the pathophysiology and stabilization of psychosis.